Checkpoint Kinase 1 Is a Key Signal Transducer of DNA Damage in the Early Mammalian Cleavage Embryo - Baran, Vladimír; Mayer, Alexandra (International journal of molecular sciences, 2023)
After fertilization, remodeling of the oocyte and sperm genome is essential for the successful initiation of mitotic activity in the fertilized oocyte and subsequent proliferative activity of the early embryo. Despite the fact that the molecular mechanisms of cell cycle control in early mammalian embryos are in principle comparable to those in somatic cells, there are differences resulting from the specific nature of the gene totipotency of the blastomeres of early cleavage embryos. In this review, we focus on the Chk1 kinase as a key transduction factor in monitoring the integrity of DNA molecules during early embryogenesis.
Keywords: Checkpoint Kinase 1; Animals; DNA Damage; zvířata; embryonální vývoj; poškození DNA; Embryo, Mammalian; embryo savčí; Embryonic Development; checkpoint kinasa 1